Freezing levels determine successful cryoablation of Ehrlich carcinoma cells. - Goltsev, A.M.; Bondarovych, M.O.; Babenko, N.M.; Gaevska, Yu.0.; Ostankov, M.V. (My University, 2019)
During cryoablation in the center and on the periphery of tumor, a significant temperature gradient is observed. The tumor cells are exposed to different temperatures, which may cause incomplete tumor destruction. The research aim was to determine the intensity of necrotic/apoptotic processes and subpopulation composition of Ehrlich carcinoma (EC) after cooling down to different temperatures. The research object was EC cells, as a model of breast cancer, which were grown for 7 days in Balb/C mice peritoneal cavity. The EC cells were frozen in ascitic fluid at a rate of 10 deg/ min down to -30°, -60°, -80° C, followed by warming in a water bath at 41°C. Аfter thawing, the number of nucleated cell, their viability, and necrotic/apoptotic cells were determined using Annexin-V (BD, USA) and PI (Sigma, USA); subpopulation composition was examined using monoclonal antibodies (BD, USA) to CD44, CD24 structures. The positive controls were the indices of native EC cells, while the negative ones were those subjected to a direct immersion into liquid nitrogen. Minimal cell viability (16.2 ± 0.7%) was observed when the sample reached -80°C, that was almost comparable to 90% cell death in negative control. In all the evaluated variants, the predominant way of cell death was necrosis, with the exception of freezing down to -30°C, whereat the number of cells in apoptosis increased significantly versus all the variants of freezing and controls. The content of the CD44+CD24-, CD44+CD24+, CD44-CD24+ subpopulations significantly decreased with a reduction in end freezing temperature, while the least differentiated CD44hi were more resistant to low temperatures. The findings indicate among all the tested options, the cooling down to -80°C caused the maximum destruction of tumor cells.
Keywords: apoptosis; Ehrlich carcinoma cells; cryoablation; subpopulations